Providing psychological assistance to Medical, Dental, and Paramedical students: Addressing the Mental Health Needs of Medical Students (Journal of Advances and Scholarly Researches in Allied Education, 2021)
We are living in a period of knowledge explosion, and the availability of healthy and competenthuman resources has become the most crucial aspect in the success of every society. None of the studieshave looked at the entire student experience in medical school. This technique aims to identify possiblestresses among kids and treat them at the proper moment. Teachers and mentors who respondedpositively agreed that these students are the future physicians of tomorrow and that, in addition toacademic and clinical training, they should be given the psychological support they require to ensuretheir well-being. Psychosocial assistance has been established as a result of the current research toassist our medical students who are having trouble fulfilling the demands of their education, training,and clinical practices. Medical schools should establish and supervise programs aimed at keeping theirstudents healthy. It will undoubtedly affect their performance and efficiency.